2013
DOI: 10.2215/cjn.03990412
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation Exposure among Kidney Transplant Recipients Due to Medical Imaging during the Pretransplant Evaluation

Abstract: SummaryBackground and objectives Kidney transplant recipients are at increased risk for malignancies. One recognized risk for malignancy is ionizing radiation. The purpose of this study was to determine, among kidney transplant recipients, the medical imaging procedures that contribute to radiation exposure and their cumulative radiation exposure, as a result of their pretransplant evaluation.Design, setting, participants, & measurements Medical records of patients who received a first, kidney-alone transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…A mean of 161 DI studies and 138 mSv effective radiation exposure were documented during a mean of 6.5 years follow-up for 107 lung transplant recipients [3]. A study of 202 heart transplant recipients followed for up to 10 years reported a mean of 66 DI studies and 84 mSv effective radiation exposure post-transplant [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mean of 161 DI studies and 138 mSv effective radiation exposure were documented during a mean of 6.5 years follow-up for 107 lung transplant recipients [3]. A study of 202 heart transplant recipients followed for up to 10 years reported a mean of 66 DI studies and 84 mSv effective radiation exposure post-transplant [14].…”
Section: Discussionmentioning
confidence: 99%
“…One study estimated that 1% of malignancies in Canada and the United States (US) are attributable to radiation from DI [2]. The maximum permissible occupational radiation exposure in the US is 50 millisievert (mSv) per year or 100 mSv over 5 years [3] while background radiation is about 3 mSv annually [4]. The lifetime excess risk of death from cancer has been estimated to increase by approximately 0.4% with 100 mSv of cumulative radiation exposure [5] and to be 5% per sievert [6].…”
Section: Introductionmentioning
confidence: 99%
“…[75][76][77][78][79][80] Even radiation, instinctively disliked by many patients, may pose a risk. Indeed, Nguyen et al 81 found in a cohort of transplanted patients, already at higher risk for malignancy, that 29% were exposed to high or very high levels of radiation in their pretransplant evaluations, and that nuclear medicine studies accounted for 83% of that exposure. The lower specificity of noninvasive testing in patients with ESRD and CKD often results in coronary angiograms without evidence of CAD.…”
Section: A Need For Randomized Trials To Evaluate Cardiovascular Scrementioning
confidence: 99%
“…However, because ionizing radiation poses a recognized risk for malignancies, the effects of multiple pre-and posttransplant radiation in the setting of immunosuppression may enhance this risk (43).…”
Section: Computed Tomographymentioning
confidence: 99%